INFECTIVE ENDOCARDITIS - Mufti, Aziz Gul; Abbas, Farhat (Journal of Ayub Medical College Abbottabad, 1998)
Infective endocarditis (IE) is a disease in which the infecting organism invades the endothelial lining of the heart and great vessels.1 Historically IE has been classified as acute or subacute on the basis of clinical course in the preantibiotic era. Acute endocarditis denotes infection on a normal valve by a highly virulent organism causing rapid destruction of the heart valves and widespread metastatic foci. Death usually occurred within six weeks. Subacute endocarditis referred to infection on an abnormal valve (usually rheumatic) with relatively avirulent organism. The course was indolent i.e. upto two years. Currently rheumatic heart disease is becoming infrequent, especially in western countries, a newer classification has been adopted. 1. Native Valve Endocarditis (NVE). 2. Prosthetic Valve Endocarditis (PVE). 3. I/V drug abuser endocarditis.